KEPEMIMPINAN KOLABORATIF DAN PARTISIPATIF DALAM MENINGKATKAN PROFESIONALISME GURU - Abidin, Zainal; Qusairi, Ahmad (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2025)
In facing the challenges of the globalization era, the quality of education is highly dependent on teacher professionalism and effective leadership in schools. Although theories on collaborative and participatory leadership have been widely developed, their implementation at the junior high school level in Indonesia is still limited and suboptimal. Therefore, this study aims to explore the influence of collaborative and participatory leadership on improving teacher professionalism at MTs Alzain Pandaan, Pasuruan, through a qualitative case study approach over a three-month period. The research method used was descriptive qualitative with a case study design. The study population included all teachers and the principal, selected through purposive sampling of ten subjects: the principal, vice principal, and eight teachers from various subjects. Data were collected using participant observation techniques, semi-structured interviews, and relevant document reviews. The research instrument was developed based on transformational leadership theory and data quality standards, and its validity and reliability were tested. Data analysis was conducted thematically through transcription, coding, and interpretation of emerging patterns. The results showed that collaborative leadership can improve open communication, active collaboration, and teacher empowerment, which significantly enhances their professionalism. These findings strengthen the argument that an inclusive leadership style can create an innovative, harmonious, and high-quality work environment. This research contributes to the literature on educational leadership and recommends longitudinal studies and the development of practical models that can be applied more broadly at the national level.